2016
DOI: 10.12980/apjtd.7.2017d6-328
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, monitoring and mapping of insecticide resistance of malaria vector, Anopheles culicifacies (Diptera: Culicidae) to different imagicides in Iran

Abstract: The journal implements double-blind peer review practiced by specially invited international editorial board members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Indoor residual spraying with bendiocarb, which started simultaneously in 1978 as that for propoxur, was used in subsequent years mostly in malaria-prone Oriental parts of Iran. One study reported female A. culicifacies s. l. partial resistance to bendiocarb and propoxur in Sistan-Baluchistan province monitoring [46]. Thus, bendiocarb was later replaced with lambda-cyhalothrin in this region, while esterases were involved in malaria vector resistance to this carbamate [47].…”
Section: Insecticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor residual spraying with bendiocarb, which started simultaneously in 1978 as that for propoxur, was used in subsequent years mostly in malaria-prone Oriental parts of Iran. One study reported female A. culicifacies s. l. partial resistance to bendiocarb and propoxur in Sistan-Baluchistan province monitoring [46]. Thus, bendiocarb was later replaced with lambda-cyhalothrin in this region, while esterases were involved in malaria vector resistance to this carbamate [47].…”
Section: Insecticidesmentioning
confidence: 99%
“…The second primary malaria vector is A. culicifacies s. l., which is a species complex with five siblings in the Oriental region of Iran extending across Pakistan into sub-continental India. It has been found to be resistant to DDT, dieldrin, and malathion while being tolerant (RC) to bendiocarb, propoxur, cyfluthrin, and deltamethrin, but susceptible to other pyrethroid insecticides in Sistan-Baluchistan province [46]. A GSTe2 (Epsilon 2) insecticide resistance gene was not detected in a study on this and two other malaria vectors in this province, A. culicifacies s. l. and A. fluviatilis s. l. [49], but confirmed in A. stephensi.…”
Section: Malaria Mosquito Vectorsmentioning
confidence: 99%
“…There are several reports of insecticide resistance in malaria and West Nile vectors in Iran [13,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Studies on non-pathogenic fungi of mosquitoes are very scarce and have not been done in Iran.…”
Section: Effects Of Fungi On Morphological or Behavioural Manifestations Of Mosquito Larvaementioning
confidence: 99%
“…Using insecticide caused resistant in the vectors. There are several reports on resistant status of malaria vectors including An.stephensi [3][4][5] An.maculipenis [6]) , An.culicifacies ( [7][8][9] ) An. [10]).…”
Section: Introductionmentioning
confidence: 99%